Implementasi Pendekatan Gamifikasi dalam Pembelajaran Fisika: Analisis Bibliometrik - Astuti, Irnin Agustina Dwi; Bhakti, Yoga Budi; Okyranida, Indica Yona; Prasetya, Rendi (Navigation Physics : Journal of Physics Education, 2024)
To enhance problem-solving skills in physics education, a learning model strategy is needed that can effectively visualize physics concepts and promote interactive learning. One of the learning approaches that can be utilized is gamification. This study aims to analyze the implementation of gamification in physics education using a bibliometric approach with the VOSViewer software. The method used in this study is bibliometric analysis. There are 5 classification clusters identified through the VOSViewer software. The results of the study show that articles using the keywords "physics education" and "gamification" have significantly increased in 2020, 2021, and 2022. From the analysis using VOSViewer, the words "physics" and "gamification" frequently appeared, indicating that there has been considerable research on gamification. However, it becomes an innovation when linked to physics education, both in terms of teaching and learning media